THE COMPARISON BETWEEN FAMA-FRENCH THREE FACTORS MODEL (FF3FM) AND CAPITAL ASSET PRICING MODEL (CAPM) AS INVESTING DECISION ON EFFICIENT SHARE (Study of LQ45 Listed In Indonesian Stock Exchange Periods of July 2010 – June 2014) - Sutan Indra Hanif; . Suhadak; Raden Rustam Hidayat (Jurnal Administrasi Bisnis, 2015)
This research aims to analyze the implementation of Fama-French Three Factors Model (FF3FM) method in Indonesia than Capital Asset Pricing Model (CAPM) , and it is not about determining the best method between CAPM and FF3FM. The research concern about the companies listed in Indonesian Stock Exchange (IDX), whose include in LQ45 period July 2010 - June 2014. The type of research in this undergraduate thesis is descriptive using quantitative approach. The collecting data method in this research is documentary, with the data of shares of the companies listed in Indonesian Stock Exchange (IDX) period July 2010 – June 2014 which include in LQ45 as population. The sampling done using purposive sampling, and generates 22 samples from 45 populations. The results show that the implementation of CAPM method generates 13 efficient shares and 9 inefficient sahres; while FF3FM generates 20 efficient shares and only 2 include in inefficient shares. In the end, the analysis shows that the FF3FM is the development of CAPM that can be seen on their same trend of SML. The main differences of CAPM and FF3FM are SMB and HML which are owned by FF3FM formula. Key Words : FF3FM, CAPM, LQ45, Share, Efficient, Inefficient